Solid Dispersion Powder of Sargassum cristaefolium extract by solvent evaporation technique - Amalia, Eri; Khairunnisa, Nada; Aghnia Khairinisa, Miski; Gozali, Dolih (Indonesian Journal of Pharmaceutics, 2024)
Sargassum cristaefolium is one of 782 types of seaweed/macroalgae that grows in Indonesia and is known as one of the macroalgae with bioactive compounds having an important role in the development of nutraceuticals for disease prevention and health maintenance. Sargassum cristaefolium extract (SCE) is known for its various beneficial activities such as antimigraine by reducing levels of CGRP and inhibitor of tyrosinase activity in anti-melanogenetics. Nevertheless, due to its hygroscopic viscous extract consistency and fishy odor, a suitable formulation is required to prepare a powder form of SCE and thus could be applied in a suitable dosage form. Our current study aims to develop the extract into suitable powder raw material by applying a solid dispersion technique.  The solid dispersion of SCE was initially prepared by selecting suitable carrier agents such as Aerosil, Microcrystalline cellulose (MCC) PH 101, maltodextrin, and PVP K30 with the extract in a ratio of 1:1, and continued by the combination of the carrier agents. The best powder formula was characterized by its powder characteristic, solubility and powder flow was assessed by its angle of repose, Carr’s index and Hausner ratio.  The experiment results that the optimum formulation for solid dispersion of SCE was obtained by the combination of SCE:PVP: MCC at a ratio of 1:1:3 with a less fishy smell, and excellent powder properties. The composite mixture was estimated due to the formation of hydrogen bonds between the carbonyl group of PVP and the hydroxyl group of SCE’s compound and MCC. In conclusion, solid dispersion of SCE by employing a combination of PVP and MCC can be an alternative to prepared SCE powder with optimum humidity protection and good flowability thus suitable to proceed as solid dosage form.  Keywords: Sargassum cristaefolium, solid dispersion, PVP K30, Microcrystalline                      cellulose PH101